ANALISIS KOMPETENSI PEDAGOGIK GURU AKIDAH AKHLAK MADRASAH ALIYAH SUNGGAL SUMATERA UTARA - Hamyar, Naila Ramadhani; Harahap, Muhammad Yunan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to measure the pedagogical competence of Aqidah Akhlak Islamiyayah Sunggal teachers with a focus on student understanding, learning design, evaluation of learning outcomes, spiritual and moral development of students. Teachers need to master teaching methods, curriculum adaptation, learning technology, and student guidance skills. With that, this study also provides an understanding that teachers must be able to motivate students, especially aqidah akhlak teachers whose job is not only to provide Islamic religious knowledge, but also to provide good and polite examples. This study is expected to contribute to improving the quality of aqidah akhlak education at Madrasah Aliyah Sunggal, with a focus on analysis on pedagogical competence in improving the teaching skills of teachers.